2015
DOI: 10.1111/imb.12184
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the functional role of thioredoxin reductase, a selenoprotein, in maintaining normal native microbiota in the Gulf Coast tick (Amblyomma maculatum)

Abstract: Tick selenoproteins have been associated with antioxidant activity in ticks. Thioredoxin reductase (TrxR), also a selenoprotein, belongs to the pyridine nucleotide-disulfide oxidoreductase family of proteins and is an important antioxidant protein. Molecular interaction between native microbiota and tick hosts are barely investigated. In this study, we have determined the functional role of TrxR in tick feeding, and maintenance of native microbial community. TrxR transcript levels remained high and microbial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 50 publications
0
55
0
Order By: Relevance
“…maculatum to offset starvation stress and blood feeding‐related stress makes it likely that it possesses a proactive antioxidant system. Complete studies of the tick interactive antioxidant network are presently still lacking, but the available literature implicates the extensive arsenal of antioxidant and redox‐associated selenoproteins in the ability of the tick to tolerate extreme alterations in redox homeostasis associated with long periods of starvation off the host, and the acquisition and digestion of blood and bloodmeal‐related products on the host (Adamson et al ., ; Budachetri & Karim, ).…”
Section: Introductionmentioning
confidence: 99%
“…maculatum to offset starvation stress and blood feeding‐related stress makes it likely that it possesses a proactive antioxidant system. Complete studies of the tick interactive antioxidant network are presently still lacking, but the available literature implicates the extensive arsenal of antioxidant and redox‐associated selenoproteins in the ability of the tick to tolerate extreme alterations in redox homeostasis associated with long periods of starvation off the host, and the acquisition and digestion of blood and bloodmeal‐related products on the host (Adamson et al ., ; Budachetri & Karim, ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, silencing thioredoxin reductase, another selenoprotein, in A. maculatum did not have a negative impact on blood feeding and reproduction. Likewise, variations in transcriptional expression of some antioxidant enzymes were also observed, suggesting compensatory mechanism in the absence of thioredoxin reductase [139]. However, the more interesting finding in that study was the decreased microbiota population following thioredoxin reductase knockdown, possibly because of disturbed redox homeostasis balance.…”
Section: Rnai Studies On Tick Protective Antigens and Immunitymentioning
confidence: 73%
“…The bacterial load in each tick tissue was estimated as described previously (Budachetri and Karim, 2015; Narasimhan et al, 2014). A slightly modified published protocol was used to estimate FLE (Dergousoff and Chilton, 2012) and CMM numbers (Sassera et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to successfully feed and survive, ticks must somehow prevent the detrimental and promote the beneficial aspects of ROS release, which suggests that precise regulatory strategies must exist for maintaining appropriate ROS levels both within the tick and possibly at the tick—host interface. Our previous studies have revealed an adaptive co-evolutionary process that enables the survival of the tick-borne pathogen Rickettsia parkeri by manipulating an antioxidant defense system associated with selenium, which includes a full set of selenoproteins and other antioxidants (Adamson et al, 2014, 2013; Budachetri et al, 2017; Budachetri and Karim, 2015; Crispell et al, 2016; Karim et al, 2011; Karim and Ribeiro, 2015; Kumar et al, 2016). ROS generation is one of the first lines of host defense against invading microbes (Ha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation